2023
DOI: 10.1039/d3nj02260a
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the kinetic behavior of microwave-assisted synthesis of NaX zeolite from lithium slag

Abstract: Lithium slag is industrial waste residue of the extraction of lithium carbonate industry, which has the issue of high output and low utilization rate. In order to improve the utilization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…According to Lin et al [10], lithium slag was used to prepare co-crystalline zeolite FAU/LTA-0 by the hydrothermal method that utilized mother liquid. It was directly used as a raw material by Huang et al [11] to synthesize NaX zeolite using a hydrothermal and microwave-assisted method, and the zeolite had smaller grains (0.5-0.8 µm) and good stability. Wang et al reported that zeolite A with excellent crystallinity can be synthesized under hydrothermal conditions using lithium slag activated by the new mild alkali fusion method [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to Lin et al [10], lithium slag was used to prepare co-crystalline zeolite FAU/LTA-0 by the hydrothermal method that utilized mother liquid. It was directly used as a raw material by Huang et al [11] to synthesize NaX zeolite using a hydrothermal and microwave-assisted method, and the zeolite had smaller grains (0.5-0.8 µm) and good stability. Wang et al reported that zeolite A with excellent crystallinity can be synthesized under hydrothermal conditions using lithium slag activated by the new mild alkali fusion method [12].…”
Section: Introductionmentioning
confidence: 99%